Delayed linkage to HIV care among asylum seekers in Quebec, Canada - Kronfli, Nadine (BMC Public Health, 2019)
BACKGROUND: Migrants represent an increasing proportion of people living with HIV in many developed countries. We aimed to describe the HIV care cascade and baseline genotypic resistance for newly diagnosed asylum seekers referred to the McGill University Health Centre (MUHC) in Montreal, Quebec, Canada. METHODS: We conducted a retrospective cohort study of patients linked to the MUHC from June 1, 2017 to October 31, 2018. We calculated the median time (days; interquartile range (IQR)) from: 1) entry into Canada to immigration medical examination (IME) (i.e. HIV screening); 2) IME to patient notification of diagnosis; 3) notification to linkage to HIV care (defined as a CD4 or viral load (VL) measure); 4) linkage to HIV care to combination antiretroviral therapy (cART) prescription; and 5) cART prescription to viral suppression (defined as a VL < 20 copies/mL). We reviewed baseline genotypes and interpreted mutations using the Stanford University HIV Drug Resistance Database. We calculated the proportion with full resistance to > 1 antiretroviral. RESULTS: Overall, 43% (60/139) of asylum seekers were newly diagnosed in Canada. Among these, 62% were late presenters (CD4 < 350 cells/μl), 22% presented with advanced HIV (CD4 < 200 cells/μl), and 25% with high-level viremia (VL > 100,000 copies/ml). Median time from entry to IME: 27 days [IQR:13;55]; IME to notification: 28 days [IQR:21;49]; notification to linkage: 6 days [IQR:2;19]; linkage to cART prescription: 11 days [IQR:6;17]; and cART to viral suppression: 42 days [IQR:31;88]; 45% were linked to HIV care within 30 days. One-fifth (21%) had baseline resistance to at least one antiretroviral agent; the K103 N/S mutation was the most common mutation. CONCLUSIONS: While the majority of newly diagnosed asylum seekers were late presenters, only 45% were linked to care within 30 days. Once linked, care and viral suppression were rapid. Delays in screening and linkage to care present increased risk for onward transmission, and in the context of 21% baseline resistance, consideration of point-of-care testing and immediate referral at IME screening should be made.